Entre o biológico e o social: discursos sobre raça na comunicação pública da ciência - Neves, Igor Oliveira (2022)
This work aims to study how the race category is biologically constructed in the discourses within the Public Communication of Science in two periods (1870-1930 and 1990-2021). In the first chapter, we review the origin of the term race in science, in Europe in the 17th and 18th centuries, and how these ideas arrived in Brazil at the end of the 19th century. We talk briefly about the period after the fall of scientific racism as a paradigm and we look at the current state of race issues in science after the Human Genome Project, also looking at the specific context of Brazil. In the second chapter we discuss the social construction of science and raise different ways of communicating science. We also tried to understand how, in the periods studied, the Public Communication of Science was characterized. Finally, we analyzed texts from Public Communication of Science vehicles that dealt directly with race. We observe that in the texts of the first period race was classified as biological and that black people were understood as inferior. In the second period, race is generally discarded as a biological category, including as an argument against the quota policy, but genetic research sometimes reaffirms biological imaginaries, as do ancestry tests. In both periods, the issue of miscegenation proved to be important for discussions about race, biology, and identity (AU)